Rewrite the expression using the definition of composite functions.
![(f\circ g)(-8)=f(g(-8))](https://img.qammunity.org/2023/formulas/mathematics/college/9rbr3nqvuwrjoj7v2rvt4mv804ai0e24hx.png)
Start from the inner function. To solve for g(-8), substitute -8 into the value of x in g(x).
![(f\circ g)(-8)=f\lbrack-(-8)-12\rbrack](https://img.qammunity.org/2023/formulas/mathematics/college/bl0k1gxx8362cdyksry47kan8s8e60jo80.png)
Simplify the expression inside the brackets.
![(f\circ g)(-8)=f(8-12)=f(-4)](https://img.qammunity.org/2023/formulas/mathematics/college/gecg6biwfgszbzqw6967shhnv5ordrprpr.png)
To find f(-4), substitute -4 into the value of x in f(x).
![(f\circ g)(-8)=(-4)^2-3(-4)-12](https://img.qammunity.org/2023/formulas/mathematics/college/ln0ghs5ds88v4kampyivdy9zmyrpd0rr9r.png)
Simplify the expression.
![(f\circ g)(-8)=16+12-12=16](https://img.qammunity.org/2023/formulas/mathematics/college/j1c65kmvpy40redtpdi7jf4njtm421bbqw.png)
Therefore, the value of the expression is 16.